Matrix‐Based Encapsulation of Construction Chemicals Using High‐Shear Agglomeration. Issue 6 (4th March 2016) - Daake, Henning von; Stascheit, Robert; Stephan, Dietmar
Abstract: Encapsulation of dry superplasticizers in matrix‐based encapsulation systems was investigated. As basic material, commercially available fly ash was granulated by high‐shear agglomeration. Due to a high variability of factors affecting the encapsulation process and later release of admixtures, the design‐of‐experiments method was applied to reduce the quantity of experiments. Statistical evaluation indicates that the particle characteristics of the agglomerates were mostly influenced by the binder viscosity during the investigations. The delayed admixture release was enhanced by high binder viscosity and low energy input during the agglomeration process due to a coating of the bigger superplasticizer particles by the smaller fly ash. These results will help to develop encapsulated construction chemicals with controlled admixture delivery for the future application in a wide range of different building materials. Abstract : Encapsulation is a common practice to enhance the material performance, for example, the admixture release behavior. In the field of construction chemicals, a controlled delivery of agents could be a good possibility to enhance the properties of materials. The high‐shear mixing technique was evaluated to encapsulate construction additives for future applications.